Metachronous Osteoid Osteoma of the Mid-Diaphysis of the Fibula and Distal Humerus: A Case Report - Adlan, Amirul; Azzopardi, Christine; Davies, Mark; James, Steven; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2022)
Osteoid osteomas are mostly solitary. We report a case of metachronous osteoid osteoma of mid-diaphysis of fibula followed by distal humeral osteoid osteoma after a 7-year interval.
Keywords: metachronous; osteoid osteoma; fibula; humerus